British tax credit simplification, the intra-household distribution of income and family consumption - Paul Fisher (University of Essex, Institute for Social and Economic Research (ISER), 2014)
The UK Government enacted simplification of its tax credit system in 2003. An inter- esting consequence of the reform is that tax credit payments were split between partners in couples, causing a rare wallet to purse transfer. This paper presents evidence on the effects of the reform on family spending, using quasi-likelihood techniques, for a sample of low income couples with children. In areas of child goods, evidence of important spending increases are found, whereas spending decreases are observed amongst goods that disproportionately ben- efit parents. A further key finding is an apparent trade-off between spending on public goods that are not exclusively consumed by children, but may nonetheless have a child development dimension. Results are contrasted to earlier findings from UK 1970s child benefit reforms. The effects are consistent with a non-cooperative bargaining framework, in which partners differ in their relative preference for different household public goods.
Keywords: C21; D12; H31; I38; J08; J16; 330; family expenditure; child well-being; welfare reform